Realiti negara dalam sajak K.H.A. Mustofa Bisri - Ida Nurul Chasanah, (Universiti Kebangsaan Malaysia, 2001)
K.H.A. Mustofa Bisri’s poems reveal social reality in Indonesia in the New Order. In his poems, state power is manifested to be dominating, be it ideology, economy, and in the ideological, beureaucratic, economic, political in Indonesia and cultural field. His poems present people who are weak and easily swayed and frauded in Indonesia during the New Order. State, in Bisri’s poems, manifested in the form of critics against it. The critics cover those of government policy, its cruelty, and its cunning characters